Layered Perovskites in Solar Cells: Structure, Optoelectronic Properties, and Device Design. Issue 24 (19th May 2021) - Sirbu, Dumitru; Balogun, Folusho Helen; Milot, Rebecca L.; Docampo, Pablo
Abstract: Layered hybrid perovskites (LPKs) have emerged as a viable solution to address perovskite stability concerns and enable their implementation in wide‐scale energy harvesting. Yet, although more stable, the performance of devices incorporating LPKs still lags behind that of state‐of‐the‐art, multi‐cation perovskite materials. This is typically assigned to their poor charge transport, currently caused by the choice of cations used within the organic layer. On balance, a compromise between efficiency and stability is sought, involving careful control of phase purity and distribution, interfaces and energy/charge transfer processes. Further progress is hindered by the difficulty in identifying the fundamental optoelectronic processes in these materials. Here, the high exciton binding energy of LPKs lead to the formation of multiple photoexcited species, which greatly complicate measurement interpretation. In this light, this review gives an overview of how complementary measurement techniques must be used to separate the contributions from the different species in order to identify device bottlenecks, and become a useful tool to narrow down the limitless list of organic cations. A move away from making compromises to mitigate the impact of poor charge transport is required. The root of the problem must be addressed instead through rational design of the interlayer cations. Abstract : Layered hybrid perovskites are a viable solution to address stability concerns in perovskite solar cells but suffer from poorer charge transport, limiting performance. This review provides an overview spanning from basic structures of the devices and materials to optoelectronic properties and stability. Additionally, it gives insights on measurement techniques currently being employed with an outlook on emerging technologies.